Differential mobilization of terrestrial carbon pools in Eurasian Arctic river basins - Feng, Xiaojuan; Vonk, Jorien E.; van Dongen, Bart E.; Örjan Gustafsson; Semiletov, Igor P.; Dudarev, Oleg V.; Wang, Zhiheng; Montluçon, Daniel B.; Wacker, Lukas; Eglinton, Timothy I. (Proceedings of the National Academy of SciencesProceedings of the National Academy of Sciences, 2013)
Mobilization of Arctic permafrost carbon is expected to increase with warming-induced thawing. However, this effect is challenging to assess due to the diverse processes controlling the release of various organic carbon (OC) pools from heterogeneous Arctic landscapes. Here, by radiocarbon dating various terrestrial OC components in fluvially and coastally integrated estuarine sediments, we present a unique framework for deconvoluting the contrasting mobilization mechanisms of surface vs. deep (permafrost) carbon pools across the climosequence of the Eurasian Arctic. Vascular plant-derived lignin phenol 14C contents reveal significant inputs of young carbon from surface sources whose delivery is dominantly controlled by river runoff. In contrast, plant wax lipids predominantly trace ancient (permafrost) OC that is preferentially mobilized from discontinuous permafrost regions, where hydrological conduits penetrate deeper into soils and thermokarst erosion occurs more frequently. Because river runoff has significantly increased across the Eurasian Arctic in recent decades, we estimate from an isotopic mixing model that, in tandem with an increased transfer of young surface carbon, the proportion of mobilized terrestrial OC accounted for by ancient carbon has increased by 3–6% between 1985 and 2004. These findings suggest that although partly masked by surface carbon export, climate change-induced mobilization of old permafrost carbon is well underway in the Arctic.